2019
DOI: 10.1016/j.molp.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

A Chromosome-Scale Genome Assembly of Paper Mulberry (Broussonetia papyrifera) Provides New Insights into Its Forage and Papermaking Usage

Abstract: Paper mulberry (Broussonetia papyrifera) is a well-known woody tree historically used for Cai Lun papermaking, one of the four great inventions of ancient China. More recently, Paper mulberry has also been used as forage to address the shortage of feedstuff because of its digestible crude fiber and high protein contents. In this study, we obtained a chromosome-scale genome assembly for Paper mulberry using integrated approaches, including Illumina and PacBio sequencing platform as well as Hi-C, optical, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 115 publications
(115 reference statements)
5
68
0
Order By: Relevance
“…For this reason, B. papyrifera is already widely used in the pharmaceutical industry. Due to its high-quality fiber, B. papyrifera is also used as important raw material for the production of paper (Peng et al 2019 ). B. papyrifera has advantages of rapid growth, strong adaptability and disease resistance, and high protein content (approximate 18–22%, including both leaves and stems) (Peng et al 2019 ), which makes it a potential candidate for new feed resourse.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, B. papyrifera is already widely used in the pharmaceutical industry. Due to its high-quality fiber, B. papyrifera is also used as important raw material for the production of paper (Peng et al 2019 ). B. papyrifera has advantages of rapid growth, strong adaptability and disease resistance, and high protein content (approximate 18–22%, including both leaves and stems) (Peng et al 2019 ), which makes it a potential candidate for new feed resourse.…”
Section: Introductionmentioning
confidence: 99%
“…4a). We detected 56 cellulose synthase (CesA) and cellulose synthase-like (Csl) genes in elephant grass, representing higher copy numbers than A. thaliana (40) and O sativa (43) 38 . Tissue expression analysis showed that 30 CesA genes had high expression levels, while 11 genes had low expression levels, and the expression levels in stems were higher than that in roots and leaves.…”
Section: Differentiation Of Biological Functions In A' and B Sub-genomementioning
confidence: 99%
“…For this reason, B. papyrifera is already widely used in the pharmaceutical industry. Due to its high-quality fiber, B. papyrifera is also used as important raw material for the production of paper (Peng et al 2019). B. papyrifera has advantages of rapid growth, strong adaptability and disease resistance, and high protein content (approximate 18-22%, including both leaves and stems) (Peng et al 2019), which makes it a potential candidate for new feed resourse.…”
Section: Introductionmentioning
confidence: 99%